Application of sequential extraction and hydrothermal treatment for characterization and enrichment of rare earth elements from coal fly ash. (15th November 2018) - Lin, Ronghong; Stuckman, Mengling; Howard, Bret H.; Bank, Tracy L.; Roth, Elliot A.; Macala, Megan K.; Lopano, Christina; Soong, Yee; Granite, Evan J.
Graphical abstract: Highlights: Seven-step sequential extraction of coal fly ash (CFA) was performed. 86% of REE in CFA were associated with the glassy phase. A process was proposed for enrichment of REE from CFA. REE were enriched from 325 mg/kg to 877 mg/kg. Abstract: Rare earth elements (REE) play a critical role in the global economy. The concern about the REE supply challenge has stimulated global interest in recovering REE from alternative non-conventional REE sources such as coal fly ash. In this paper, sequential extraction, physical separations and hydrothermal alkaline treatment were explored for characterization and enrichment of REE from coal fly ash. Seven-step sequential extraction of coal fly ash has demonstrated that 86.1% of total REE were associated with the glassy phase of the fly ash, with the remaining REE mainly distributed in the organic and sulfides phase (8.3%), the exchangeable phase (3.7%), and the carbonates phase (1.5%). A process combining physical separations, namely, particle size separation and magnetic separation, and hydrothermal alkaline treatment was proposed for enrichment of REE from coal fly ash. The optimal hydrothermal alkaline treatment condition was determined. It was demonstrated that NaOH concentration, solid-to-liquid ratio, temperature, and reaction duration had significant influence on ash dissolution in NaOH solution. Grinding could also enhance ash dissolution during subsequent hydrothermal alkaline treatment. REE were enriched from coal fly ash from 325 mg/kg to 877 mg/kg via the proposed process under optimal hydrothermal alkaline treatment conditions.